Corelations Quality of Eldery and Regional Socio-Economic Indicators in Indonesia - Risky Primastuti; Sukamdi; Umi Listyaningsih (PT FORMOSA CENDEKIA GLOBAL, 2023)
Every region has various features, one of which is the condition of the elderly in Indonesia where there are have gaps between regions. In addition to the features of the elderly, the socio-economic conditions of each province also diverse. So that policies of older peolpe can be right on target, his further research aims to assess the quality categories of the elderly and test how they relate to regional socio-economic indicators. The unit of analysis for this research is 34 provinces in Indonesia, with data sources from BPS publications (Susenas and Sakernas 2021). Examination of the quality of the elderly was carried out by means of non-hierarchical K-means clustering, classification of socio-economic conditions is done by scoring HDI, per capita income, and poverty in an area ,while the correlation of the quality of the elderly with socio-economic indicators was carried out by Spearman rank analysis. The results of this study indicate that in 2021 there will be 19 provinces with poor elderly quality, six provinces with good elderly quality, and 19 provinces with good elderly quality. There is a significant, quite strong, and one-way relationship between socio-economic conditions and the quality of provincial elderly in Indonesia. The HDI and GRDP Per capita have a significant, fairly strong, and in-line relationship with the quality of the provincial elderly. Meanwhile, the proportion of poor people has a significant, quite strong, but contradictory relationship with the quality of the provincial elderly